Bicentenario de Centroamérica : historias comunes, luchas y transformaciones (Tailbooks : CLACSO, 2021)
Throughout two hundred years of autonomy in Central America, it has been sufficiently demonstrated that the pretensions of independence, despite being consolidated on the political plane, did not pay to generate change in social and economic structures. Abundant analyzes point to the recurrent lack of vision and will to redirect the path of the Central American countries. Where is the region? What perspectives can be visualized from the conditions with which one lives daily? Are there alternatives that correct the excesses of the current system and that reorient or transform it? These and others are the questions that motivate and stimulate the fifteen essays that make up this collective book, winners of the call organized by the Executive Secretariat of CLACSO and the member centers of Central America in order to value the relevance of the knowledge produced by the researchers.